Constructing a diversified online neurology teaching model under the COVID-19 - Yang, Haojun; Fan, Yishu; Chen, Zhuohui; Zhang, Shiyu; Wu, Haiyue; Hu, Xinhang; Wu, Tong; Zhang, Mengqi (Frontiers in Medicine, 2023)
Purpose To construct a diversified and comprehensive network teaching model to provide highly qualified medical teaching in neurology under COVID-19 pandemic. Materials and methods Published studies on medical education were systematically reviewed and summarized. Based on previous studies and our experience, we constructed a novel online neurology teaching model and applied it to real scene. Students taking traditional in class lessons and online lessons were asked to finish the test, respectively, to compare the efficiency of learning. Questionnaires were designed and assigned to get the feedback from students. Results The average test score of students who take online class (84.27 ± 4.64) was significantly higher than those who take in class lessons (82.08 ± 6.17) (P < 0.01). According to the feedbacks from students, online classes were more attractive to students than the conventional one. Conclusion Traditional single-mode teaching can no longer meet the needs of current medical education, especially under the rampant epidemic. This novel teaching mode, which orchestrates high-tech tools, diverse teaching methods and traditional teaching concepts, provides the solution to the challenge faced by traditional medical education. We believe that this novel online teaching mode will boost neurology education and inspire educators in other fields during this tough period.